2015
DOI: 10.1016/j.electstud.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Space matters: Geographic variability of electoral turnout determinants in the 2012 London mayoral election

Abstract: Abstract:Electoral participation is an important measure of the health of a liberal democracy. The determinants of voter turnout have been examined across a range of elections, but geographical approaches are relatively rare and are mostly performed at large scale aggregations and for national elections. This paper addresses this gap by exploring geographic variability in relationships between the turnout at a local election and socio-demographic variables at a detailed spatial level. Specifically, we focus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 47 publications
2
30
2
1
Order By: Relevance
“…For example, voting behavior differs in individuals with a high profile in terms of income and education, as well as by age groups and those with low incomes and educational levels. In addition, the participation rate of older people in elections is different from that of the youth (Leighley and Nagler, 1992;Lipset, 1960;Mansley and Demsar, 2015;Pattie and Johnston, 1998). However in our study age factor has been reported to have no impact on the elections.…”
Section: Resultscontrasting
confidence: 74%
“…For example, voting behavior differs in individuals with a high profile in terms of income and education, as well as by age groups and those with low incomes and educational levels. In addition, the participation rate of older people in elections is different from that of the youth (Leighley and Nagler, 1992;Lipset, 1960;Mansley and Demsar, 2015;Pattie and Johnston, 1998). However in our study age factor has been reported to have no impact on the elections.…”
Section: Resultscontrasting
confidence: 74%
“…Mansley and Demšar, 2015, Brunsdon et al, 1996, Fotheringham et al, 2013, as well as physical geography and ecology (e.g. Atkinson et al, 2003, Clement et al, 2009, Harris et al, 2010, Jetz et al, 2005, proving the suitability of this tool to provide an explanatory approach in spatially varying relationships (Páez et al, 2011).…”
Section: Global Vs Local Regression Modelmentioning
confidence: 99%
“…Moran's I was implemented on both the global and local models, with two tests being undertaken for robustness: Inverse Distance Squared and Queen's Case (Table 3). It can be seen through the higher Moran's I score that there was more variation in the global models when compared to the local models, which suggests that GWR was the correct tool for this analysis [77]. There are extreme variations for all independent variables in the local results, with these variations highlighting that spatial heterogeneity is occurring, while also suggesting that certain locations are outliers.…”
Section: Spatial Autocorrelationmentioning
confidence: 91%
“…Moran's I was implemented on both the global and local models, with two tests being undertaken for robustness: Inverse Distance Squared and Queen's Case (Table 3). It can be seen through the higher Moran's I score that there was more variation in the global models when compared to the local models, which suggests that GWR was the correct tool for this analysis [77].…”
Section: Spatial Autocorrelationmentioning
confidence: 94%